Teaching Factory Model Development in Vocational High Schools - Akbarul Kautsar; Giri Wiyono; Muji Mulia; Muhammad Iqbal; Muhajir Al-Fairusy (STAI Hubbulwathan Duri, 2022)
This study aims to find a conceptual model of teaching factory in the field of air conditioning and air conditioning engineering in vocational high schools (VHS). The teaching factory development model is expected to have a solid legal foundation and be able to carry out independent financial management so that they are able to carry out sound business practices. This study uses a type of development research, namely research and development (R D), with a 4-D (Four-D) approach. The stages in this research are define, design, development, and disseminate. The conceptual model of the teaching factory was tested for feasibility by the validator of material experts (expert judgment) and the model user, namely by the executor of the teaching factory in the field of refrigeration and air conditioning engineering at VHS 1 Magelang. The results of the study indicate that the teaching factory conceptual model consists of components, namely 1) information technology; 2) PPK-BLUD; 3) HR; 4) block schedule; 5) worksheets; 6) products/services; 7) workshops; 8) industry partnerships; and 9) system management. Based on the results of expert validation and model user responses, the teaching factory conceptual model was declared feasible to be applied in VHS. The teaching factory conceptual model has a solid legal foundation, allows for independent financial management patterns, and can carry out healthy business practices on an ongoing basis (sustainability).